Interaction, communication and development: Psychological development as a social process - Psaltis, Charis; Zapiti, Anna (Hove : Taylor & Francis Group, 2014)
For decades there has been considerable interest in the ways that interactions between children can provide a beneficial context for the study of cognitive and social development. In this book Psaltis and Zapiti use both theoretical and empirical research to build on the perspectives of Piaget, Vygotsky, Moscovici, and others including the legacy of Gerard Duveen, to offer a state of the art account of research on the themes of social interaction and cognitive development. Interaction Communication and Development discusses the significance of social identities for social interaction and cognitive development. The empirical set of studies presented and discussed focus on patterns of communication between children as they work together to solve problems. Communications are examined in detail with a focus on: Socio-cognitive conflict, conversational moves and conversation types. The way the different forms of the interactions relate to different sources of asymmetry in the classroom. The way social representations and social identities of gender are negotiated in the interaction. This book provides an important account of how children develop through different kinds of social interactions. It will have considerable appeal for researchers in the fields of developmental psychology, socio-cultural psychology, social representations theory and education who wish to gain a deeper understanding of development and its relation to socio-cultural processes.
1. A genetic perspective on interaction and development -- 2. Varieties of the social -- 3. The development of representations through communication -- 4. Conversation types and interaction types: microgenesis of knowledge -- 5. From one interaction to another: from microgenesis to ontogenesis -- 6. Peer interaction and cognitive development: the role of gender at 6-7 and 10-11 years old -- 7. Conclusions: towards a genetic social psychology.
Keywords: SOCIAL INTERACTION IN CHILDREN